The effect of multiplicative noise on the exact solutions of nonlinear Schrödinger equation - Abdelrahman, Mahmoud A. E.; Mohammed, Wael W.; Alesemi, Meshari; Albosaily, Sahar (AIMS mathematics, 2021)
We consider in this paper the stochastic nonlinear Schrödinger equation forced by multiplicative noise in the Itô sense. We use two different methods as sine-cosine method and Riccati-Bernoulli sub-ODE method to obtain new rational, trigonometric and hyperbolic stochastic solutions. These stochastic solutions are of a qualitatively distinct nature based on the parameters. Moreover, the effect of the multiplicative noise on the solutions of nonlinear Schrödinger equation will be discussed. Finally, two and three-dimensional graphs for some solutions have been given to support our analysis.